ERGONOMI DALAM BIDANG PERENCANAAN ARSITEKTUR DAN INTERIOR - Setiadi G S (Universitas Trisakti, 2007)
Abstract:Usage of mind and mind of being* taking care of continuity of life hear culture as we know now. From here grows various norms institutions, behaviour pattern, image of human being, including in its the process of scheme of interior and architecture. To pass off interaction and communications with the environment of human beings is provided by 3 fundamental abilities namely: structural body/anatomy, physical ability, and physichological ability. Ergonomi as applied sciences which is in altidisiplined can be entangled further as part ofscheme process.Keywords: ergonomic, hit man beings, space and environmentAbstrakPenggunaan akal dan pikiran manusia untuk menjaga kelangsungan hidupnya melahirkan apa yang kita kenal sebagai kebudayaan dari sinilah berkernbang berbagai pranata norma, pola tingkah laku, citra manusia, termasuk pula didalamnya proses perancangan arsitektur dan interior. Untuk melangsungkan komunikasi dan interaksi dengan lingkungannya manusia dibekali dengan 3 kemampuan pokok yakni: struktur tubuh/anatomi, kemampuan fisik, dan kemampuan psikis. Ergonomi sebagaiterapan yang multidisiplin dapat dilibatkan lebih jauh lagi sebagai bagian dari proses perancangan.